The development of live biotherapeutics against Clostridioides difficile infection towards reconstituting gut microbiota - Yongrong Zhang; Ashley Saint Fleur; Hanping Feng (Gut Microbes)
Clostridioides difficile is the most prevalent pathogen of nosocomial diarrhea. In the United States, over 450,000 cases of C. difficile infection (CDI), responsible for more than 29,000 deaths, are reported annually in recent years. Because of the emergence of hypervirulent strains and strains less susceptible to vancomycin and fidaxomicin, new therapeutics other than antibiotics are urgently needed. The gut microbiome serves as one of the first-line defenses against C. difficile colonization. The use of antibiotics causes gut microbiota dysbiosis and shifts the status from colonization resistance to infection. Hence, novel CDI biotherapeutics capable of reconstituting normal gut microbiota have become a focus of drug development in this field.